Investigating a Hypothetical Semiconductor Laser Bar with a Smile-shaped Temperature Profile Using a Laser Diode Simulation/Emulation Tool (Global Journals of Research in Engineering, 2013)
In this paper, Barlase, a semiconductor laser diode emulation tool, is used to emulate the by-emitter degradation analysis of high power semiconductor laser diodes. Barlase is a software that uses a LabView control interface. We have already demonstrated how Barlaseworks using a hypothetical laser diode bar (multiple emitters) to validate the usefulness of the tool. It should however, be noted that, this scenario is valid for devices at the start of the aging process only. This scenario was investigated to demonstrate Barlase as follows: curved temperature (smile) profile with maximum temperature at the centre of the bar. The result of this simulation scenario shows the successful implementation of Barlase in the by-emitter analysis of laser diodes.
Keywords: by-emitter; emitter; defect; smile-shaped temperature profile; emitter power; quantum well; degradation; threshold current; slope efficiency; band gap